2015
DOI: 10.1075/lia.6.2.04vei
|View full text |Cite
|
Sign up to set email alerts
|

Orthographic bias in L3 lexical knowledge

Abstract: In this paper, we examine some of the factors that might influence the accessing of meanings of written and spoken L3 words. We tested learners of L3 French who had Finnish as their L1 and were highly competent in L2 English. They were presented with L3 French words in written and spoken form, and were asked to give a possible translation for the target word in L1 and to rate their level of confidence in the meaning given. Because of their instructional learning background, we expected orthographic forms to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Whether the findings on activation of orthographic information apply to more naturalistic L2 spoken word processing contexts remains a question for future research. Huhta et al, 2002) in a previous study (Veivo et al, 2015) showed that self-reported proficiency scores based on the CEFR scale correlated highly with DIALANG test results. 2.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Whether the findings on activation of orthographic information apply to more naturalistic L2 spoken word processing contexts remains a question for future research. Huhta et al, 2002) in a previous study (Veivo et al, 2015) showed that self-reported proficiency scores based on the CEFR scale correlated highly with DIALANG test results. 2.…”
Section: Discussionmentioning
confidence: 95%
“…There is evidence that orthography can help to acquire new phonemic categories of the L2 (Escudero et al, 2008(Escudero et al, , 2014Showalter & Hayes-Harb, 2013;Simon, Chambless, & Kickhöfel Alves, 2010), but can also have a negative impact on the acquisition of L2 phonology (Bassetti, 2007;Bassetti & Atkinson, 2015;Young-Scholten & Langer, 2015), especially when the grapheme-phoneme relations of the L2 are different from the L1 (Escudero & Wanrooij, 2010;Hayes-Harb et al, 2010). Furthermore, there is evidence that late L2 learners in instructed learning environments can have an orthographic bias in their lexical knowledge, especially in the recognition of decontextualized word forms (Veivo, Suomela-Salmi, & Järvikivi, 2015). At the same time, words for these learners can have imprecise phonological representations (Cook & Gor, 2015;Cook, Pandža, Lancaster, & Gor, 2016), which may lead not only to the activation of false semantic content (Cook et al, 2016) but also to increased lexical competition (Broersma & Cutler, 2011).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Claims by (Veivo et al 2018(Veivo et al , 2015Veivo and Jarvikivi 2013) may offer additional context for the facilitative effect of cross-modal priming with the mismatching of written and audio forms involving phonological alternations. For example, they argue that there is often a bias towards orthographic information in L2 lexical representations, where instructional learning can lead to written forms being more established than phonological forms.…”
Section: Production Ofmentioning
confidence: 99%